The Influence Of Prices, Promotions And Product Quality On Sales Volume In Trimoda Textile In Pringsewu - Ferdi Setiawan; Tri Lestira Putri Warganegara (Cita konsultindo, 2024)
Trimoda Textile is one of the businesses engaged in the textile trade which continues to grow well by providing quality products and trends to win the competition in similar companies. This research will examine the influence of price, promotion and product quality on sales volume at Trimoda Textile in Pringsewu. The research objective was to analyze the effect of price, promotion and product quality on sales volume at Trimoda Textile in Pringsewu. The populations in this study were consumers at Trimoda Textile in Pringsewu who were observed for 1 month with an average number of 353 people or 4,236 people per year and a sample of 353 people. Data collection tool using a questionnaire, data analysis using multiple linear regression analysis. Based on the research results, it can be seen that the value of Count Which is 91,013. When compared to Ftable at a significant level of 95% and α = 0.05, which is 2.6049, then Fcount = 91,013 > Ftable = 2.6049 So it can be concluded that there is a positive and significant influence between price, promotion and product quality together on sales volume of Trimoda Textile in Pringsewu.